Reply to: Potential of 188Re as an alternative to 177Lu and dosimetric consequences: letters to the editor - Cardinale, Jens; Giesel, Frederik L.; Wensky, Christina; Rathke, Hendrik; Haberkorn, Uwe; Kratochwil, Clemens (Journal of nuclear medicine, 2023)
REPLY: In our recent publication about the preclinical development and clinical translation of 99mTc- and 188Re-PSMA-GCK01, we consciously withheld the presentation of dosimetry estimates, despite having serial planar images of patients available ([1][1]). One reason is the limited quantitative
Im Titel sind die Zahlen "188" und "177" hochgestellt
Gesehen am 28.01.2025